Framed in death - Robb, J. D., 1950- (New York : St. Martin's Press, 2025)
In Manhattan$1 (Bs cutthroat art world, a bitter, overlooked artist vows to make the city notice him. By morning, his promise is kept in blood: two gallery owners are found dead outside their home. Lt. Eve Dallas must untangle jealousy, ambition, and obsession to catch a killer who craves recognition.s
Keywords: Dallas, Eve (Fictitious character) -- Fiction; Art museums -- Fiction; Artists -- Fiction; Homicide -- Fiction; Homicide investigation -- Fiction; Murder -- Investigation -- Fiction; Manhattan (New York, N.Y.) -- Fiction; Detective and mystery fiction